The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1590/s0080-623420150000800013
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do curso de gerenciamento online na perspectiva dos egressos

Abstract: Avaliação do curso de gerenciamento online na perspectiva dos egressos Evaluación del curso gestión online desde la perspectiva de los egresos aBStract Objective: To evaluate the online course from the perspective of e-learners as well as the relation between variables. Method: A quantitative, descriptive and exploratory study. Results: After three years, the satisfaction rates in the three listed categories presented an average rate higher than 75%. The coefficients indicated a high consistency of the questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
(13 reference statements)
0
4
0
4
Order By: Relevance
“…28 Interactive tools such as forums, chats, e-mails, and others are usually available in VLE platforms, since they are organized spaces for didactic-pedagogical purposes that, combined with the teachers' and tutors' work, have contributed to a more interactive format in remote education. [29][30] The online course of this study on Health Education in Diabetes Mellitus was developed with four modules, text and article reading and interpretation, resolution of case studies, chats, forums, wherein the participants were assisted by teachers and tutors responsible for the course's organization and for monitoring in the institutional VLE. In general, the Nursing students evaluated that the features were met; however, less than two percent indicated that these features were partially met.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Interactive tools such as forums, chats, e-mails, and others are usually available in VLE platforms, since they are organized spaces for didactic-pedagogical purposes that, combined with the teachers' and tutors' work, have contributed to a more interactive format in remote education. [29][30] The online course of this study on Health Education in Diabetes Mellitus was developed with four modules, text and article reading and interpretation, resolution of case studies, chats, forums, wherein the participants were assisted by teachers and tutors responsible for the course's organization and for monitoring in the institutional VLE. In general, the Nursing students evaluated that the features were met; however, less than two percent indicated that these features were partially met.…”
Section: Discussionmentioning
confidence: 99%
“…To supply for this demand, it is recommended to use forums, in other words, an asynchronous communication tool used to share discussions of the topics proposed by professors and tutors, not necessarily occurring at the same time. 27,30 With respect to the interaction, one study 38 demonstrated that the ways for interaction and support among those individuals involved in the online educational environment are extremely valuable. The leading role of the tutor in the platform, especially by promoting unique relationships among human beings, such as motivation and encouragement for students to participate in the activities and also to offer improvements in the reflective process through sharing experiences was pointed out.…”
Section: Discussionmentioning
confidence: 99%
“…Descrever o projeto, desenvolvimento e avaliação de uma simulação multimedia interativa baseada na Web para o desenvolvimento de competências de enfermeiros em cuidados de enfermagem agudos. Evaluation of the online management course from the perspective of former students (16) . 2015…”
Section: Métodosunclassified
“…O desempenho do tutor atingiu os maiores índices de satisfação, sendo também identificada correlação positiva entre essa categoria e a categoria de auto avaliação, em outras palavras, quanto maior a satisfação em relação ao desempenho do tutor, melhor a avaliação do estudante em relação ao seu desempenho (16) . Estudo aponta que a atitude dos tutores tem efeito significativo na satisfação percebida pelos estudantes.…”
Section: Categoria 2 Atuação Do Tutor/professor Na Plataforma De Ensinounclassified
“…Muitos cursos presenciais e a distância são avaliados somente por meio da avaliação da reação, como por exemplo a avaliação do curso de atualização on-line na temática de Gerenciamento em Enfermagem realizado por Souza et al (2015). Por isso, sugere que mais estudos relacionem o nível de reações com os demais níveis de avaliação, especialmente em ações educacionais a distância, pois embora a reação seja o nível de avaliação mais estudado na área de TD&E, não há tantas pesquisas que a integrem com outros níveis, como aprendizagem e insumos.…”
Section: Reaçãounclassified